Pengaruh Pengukusan Terhadap Kandungan Oryzanol dan Perubahan Sifat Kimia Minyak Bekatul Padi Unggul Selama Penyimpanan - Y. Marsono (agriTECH, 1997)
Rice brans of three superior rice cultivars (IR-64, PB-36 and Cisadane) were steamed at 100 °C for 15 min, extruded and dried in an oven at 40-50 °C then stored in plastic containers at the ambient temperature for three months. Changes in rice bran oil and the oryzanol contents as well as chemical properties oh the oil after steaming and storage were investigated. In all rice cultivars investigated steaming increased oil content of the rice bran. The process decreased free fatty acid and Iodine values, but increased the peroxide value of the oil extracted from rice brans. Te oryzanol content of rice oils were relatively constant. During three months storage at the ambient temperature, the oil were content decreased but the oryzanol tended to increase. Iodine value of the oil extracted from rice brans significantly decreased, peroxide value increased until the second month but then decreased in the last month. Free fatty acids gradually increased during the storage time.